2020
DOI: 10.3844/ojbsci.2020.157.165
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biological Profiles and Chemical Contents of Ethanolic Nest Entrance Extracts of Thai Stingless Bees Tetrigona apicalis

Abstract: Tetrigona apicalis is a species of stingless bees found in Lower Northern Thailand. They normally construct their nest entrances as an external structure for protecting themselves from enemies. Their biological properties have not well characterized yet. The objectives of this study were to evaluate the antibacterial, antifungal and antiproliferative activities of their nest entrances. Samples were collected from four provinces and then extracted using 70% ethanol, finally called as ethanolic Nest Entrances Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Hydroquinine is an organic compound that has been shown to possess antimicrobial properties [ 10 ]. Kraikongjit et al (2018) [ 11 ] and Jongjitvimol et al (2020) [ 12 ] have previously demonstrated that ethanolic nest entrances extracts from Tetrigona apicalis exhibit antibacterial, antifungal, and anti-proliferative activities [ 11 , 12 ]. Interestingly, one of the key chemical compounds found from the extracts was the polyphenol, hydroquinine.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroquinine is an organic compound that has been shown to possess antimicrobial properties [ 10 ]. Kraikongjit et al (2018) [ 11 ] and Jongjitvimol et al (2020) [ 12 ] have previously demonstrated that ethanolic nest entrances extracts from Tetrigona apicalis exhibit antibacterial, antifungal, and anti-proliferative activities [ 11 , 12 ]. Interestingly, one of the key chemical compounds found from the extracts was the polyphenol, hydroquinine.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroquinine, an alkaloid organic compound found in particular natural products [ 28 , 29 , 30 ], was recently reported to inhibit and kill drug-sensitive (DS) and MDR strains of P. aeruginosa [ 31 ]. In addition, other alkaloid compounds have been reported to possess antimicrobial properties and anti-virulence factors in both Gram-positive and Gram-negative bacteria, such as inhibition of QS signaling and pigment production in P. aeruginosa [ 26 ], inhibiting biofilm formation in E. coli and P. aeruginosa [ 24 ] and inhibiting virulence gene expression in S. aureus [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many natural compounds have been used for ocular therapies because of their antiinfective and anti-inflammatory properties [24]. Interestingly, hydroquinine is a natural substance that has been shown to possess antimicrobial properties [25,26]. Kraikongjit et al (2018) [25] and Jongjitvimol et al (2020) [26] have previously demonstrated that hydroquinine is one of the key substances in the ethanolic nest entrance extracts from Tetrigona apicalis that exhibit antibacterial, antifungal, and anti-proliferative activities [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, hydroquinine is a natural substance that has been shown to possess antimicrobial properties [25,26]. Kraikongjit et al (2018) [25] and Jongjitvimol et al (2020) [26] have previously demonstrated that hydroquinine is one of the key substances in the ethanolic nest entrance extracts from Tetrigona apicalis that exhibit antibacterial, antifungal, and anti-proliferative activities [25,26]. Moreover, hydroquinine has anti-malarial and anti-melanin activities, which may be used for reducing light-brown skin patches and skin discoloration associated with pregnancy [27].…”
Section: Introductionmentioning
confidence: 99%